A Rapid Spectrophotometric Determination of Nitrite in Polluted Water - Hemantha Kumar, M.S.; Nagaraja, P.; Rangappa, K.S.; Suresh, A.S. (Asian Journal of Chemistry, 2010)
A new sensitive spectrophotometric method is developed for the determination of nitrite with imipramine hydrochloride coupled with 3-methyl-2-benzothiazolinone hydrazone hydrochloride in acid medium. Beer's law obeyed in the range of nitrite concentration of 0.02-7 μg/mL and the molar absorptivity at 640 nm is 0.49 x 1041 mole–1 cm–1. Results obtained by using the proposed method for water samples agree well with those obtained by Saltzman standard method.